The Study of the Poetics and Creative Method of I. Repin Based on the Material of the Sketches for the "State Council" from the Collection of the Kharkiv Art Museum - Shylo, Oleksandr (HUDPROM: The Ukrainian Art and Design Journal, 2024)
The Kharkiv Art Museum owns two preparatory sketches for the painting by I. Repin “The solemn meeting of the State Council on May 7, 1901, on the day of the centenary anniversary of its foundation” (1901–1903) – portraits of infantry general P. Hudym-Levkovych and infantry general P. Vannovsky. They are rightfully considered masterpieces and gems of the museum’s collection. Their examination gives us a reason to reflect on the problems of the creative method and poetics of their author. “State Council” became a synthesis of both artistic and worldview searches that accompanied Repin throughout his previous creative path. The place of this work in Repin’s creative biography and in the artistic culture of his time is such that it is simultaneously a work of historical genre, a group portrait, a complex composition from the field of high society life, and an aesthetic manifesto. All this together turns it and a set of sketches for it into a multifaceted artistic ensemble. The masterpiece was created during the deep crisis of European realism in the 19th century. Repin was one of the greatest representatives of this direction in Fine Art at that time. The change in worldview orientations stemmed from the very logic of the development of his work and was a consequence of those internal contradictions that accumulated in the development of European realism in the 19th century. For Repin’s poetics, the task of portraits similar to this ensemble lies in the desire to recreate a person in the greatest intensity of expression of his character. The painting and the sketches for it embody Repin’s search for new artistic beauty, which denied the previously accumulated experience. It was all the more dramatic if you take into account that Repin was aware of his status as a leader in the art of the second half of the 19th century. With the “State Council” ensemble, which was created at the turn of the century, Repin manifested his artistic program, open to the future.